Catalytic layer of high-temperature proton exchange membrane fuel cell and preparation method thereof

By introducing quaternized polybenzimidazole (QAPBI) into the catalytic layer of the high-temperature proton exchange membrane fuel cell, the phosphoric acid is fixed in the proton exchange membrane using its strong intermolecular force with phosphoric acid, which solves the problems of uneven distribution of phosphoric acid and migration loss, and improves the performance and stability of the fuel cell.

CN119786632APending Publication Date: 2025-04-08SHANGHAI INST OF SPACE POWER SOURCES

Patent Information

Application Number
CN202411790808.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In high-temperature proton exchange membrane fuel cell, the distribution of phosphoric acid in the catalytic layer is uneven, resulting in the cover of the active sites of the catalyst, affecting the efficiency of electrochemical reactions, and the phosphoric acid is easily migrated and lost, reducing the performance and stability of the fuel cell.

Method used

By introducing quaternized polybenzimidazole (QAPBI) into the catalytic layer, the phosphoric acid is immobilized in the proton exchange membrane using its strong intermolecular force with phosphoric acid, and its distribution is regulated, reducing coverage and migration loss of catalyst active sites.

Benefits of technology

It effectively improves the proton transfer efficiency of the proton exchange membrane, reduces the coverage of catalyst active sites, and enhances the performance and stability of fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786632A_ABST
    Figure CN119786632A_ABST
Patent Text Reader

Abstract

The invention discloses a catalyst layer of a high-temperature proton exchange membrane fuel cell and a preparation method thereof, and the method comprises the following steps: step 1, taking glycidyl trimethyl ammonium chloride and polybenzimidazole as reactants, and carrying out quaternization reaction to obtain quaternized polybenzimidazole; step 2, mixing the quaternized polybenzimidazole, a binder and a catalyst to obtain a uniform catalyst slurry; and step 3, coating carbon paper with the uniform catalyst slurry to obtain the catalyst layer. The catalyst layer prepared by the method can effectively adjust the distribution of phosphoric acid in the catalyst layer, reduce the coverage of phosphoric acid on catalyst active sites, reduce the migration and loss of phosphoric acid from a proton exchange membrane, and ensure the proton transfer efficiency of the proton exchange membrane, thereby improving the performance and stability of the high-temperature proton exchange membrane fuel cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of high-temperature proton exchange membrane fuel cells, and in particular to a catalyst layer of a high-temperature proton exchange membrane fuel cell and a preparation method thereof. Background Art

[0002] Proton exchange membrane fuel cell (PEMFC) is a highly efficient energy conversion device that can directly convert chemical energy into electrical energy. It has the advantages of high power density, environmental friendliness, fuel renewable, and a wide range of applications. Proton exchange membrane fuel cells (PEMFC) are divided into low-temperature proton exchange membrane fuel cells (LT-PEMFC) and high-temperature proton exchange membrane fuel cells (HT-PEMFC). PEMFC with an operating temperature of 100℃-200℃ is HT-PEMFC. Compared with commercial LT-PEMFC, HT-PEMFC has the advantages of simple water and heat management, strong carbon monoxide tolerance, and high cogeneration efficiency.

[0003] Membrane electrode (MEA) is the core component of high-temperature proton exchange membrane fuel cells (HT-PEMFC), which includes proton exchange membrane, catalyst layer, gas diffusion layer, etc. Its main function is to achieve efficient electrochemical reaction and energy conversion in fuel cells. The catalyst layer, as the place where the chemical reaction occurs, is mainly composed of catalysts, carbon-based catalyst carriers, adhesives, and proton conductive materials (such as phosphoric acid), which plays a vital role in determining the performance of fuel cells.

[0004] Phosphoric acid, as a liquid electrolyte, is distributed in the proton exchange membrane and acts as a proton conductor in the high-temperature proton exchange membrane fuel cell, ensuring rapid proton conduction. Although a high content of phosphoric acid can improve proton conductivity, it will be redistributed in the catalyst layer under current drive, thus affecting the performance of the high-temperature proton exchange membrane fuel cell. On the one hand, phosphoric acid will contact the catalyst in the catalyst layer and form a liquid film on its surface. This liquid film covers the active sites of the catalyst, hindering the contact between the reaction gas (such as oxygen or hydrogen) and the catalyst, reducing the effective three-phase interface and reducing the reaction activity of the catalyst; on the other hand, the uneven distribution of phosphoric acid in the catalyst layer will increase the material transfer resistance in the catalyst layer; on the other hand, due to the hydrogen bonding between water molecules and phosphoric acid, phosphoric acid can easily migrate and lose from the proton exchange membrane along with the water molecules generated in the reaction gas, which may cause deformation or damage to the membrane structure, thereby reducing the proton transfer efficiency of the proton exchange membrane and affecting the output power and stability of the fuel cell.

[0005] Therefore, in order to improve the performance of high-temperature proton exchange membrane fuel cells, it is necessary to adjust the distribution of phosphoric acid in the catalytic layer to reduce its coverage of the active sites of the catalyst, while reducing the migration and loss of phosphoric acid to improve the performance and stability of high-temperature proton exchange membrane fuel cells. Summary of the invention

[0006] The purpose of the present invention is to introduce quaternized polybenzimidazole (QAPBI) into the catalyst layer, so that the strong intermolecular force between the quaternary ammonium polybenzimidazole and phosphoric acid can fix the phosphoric acid in the proton exchange membrane, reduce the coverage of phosphoric acid on the active sites of the catalyst, and reduce the migration and loss of phosphoric acid, thereby ensuring the proton transfer efficiency of the proton exchange membrane and improving the performance of the fuel cell.

[0007] In order to achieve the above object, the present invention provides a method for preparing a catalyst layer of a high-temperature proton exchange membrane fuel cell, the method comprising:

[0008] Step 1, using glycidyl trimethyl ammonium chloride and polybenzimidazole as reactants to undergo a quaternization reaction to obtain a quaternized polybenzimidazole;

[0009] Step 2, mixing the quaternized polybenzimidazole, the binder and the catalyst to obtain a uniform catalyst slurry;

[0010] Step 3: coating the uniform catalyst slurry onto carbon paper to obtain a catalyst layer.

[0011] Optionally, in step 1, the temperature of the quaternization reaction is 90° C.-100° C., and the time is 12 h-14 h.

[0012] Optionally, in step 1, the mass ratio of glycidyl trimethyl ammonium chloride to polybenzimidazole is (1-2): (98-99).

[0013] Optionally, in step 2, the binder comprises at least one of polytetrafluoroethylene, perfluorosulfonic acid resin, and vinylidene fluoride-hexafluoropropylene copolymer, and the catalyst comprises at least one of a platinum-based catalyst and a platinum alloy catalyst.

[0014] Optionally, in step 2, the mass ratio of the quaternized polybenzimidazole to the binder is 1:(1-5).

[0015] Optionally, in step 2, the mass fraction of the total mass of the quaternized polybenzimidazole and the binder in the uniform catalyst slurry is 20%-30%.

[0016] Optionally, in step 2, the mixing includes stirring and ultrasonic cycles, a single stirring time is 10 min-20 min, and a single ultrasonic time is 15 min-60 min.

[0017] Optionally, in step 3, the coating method is any one of spraying, dipping, and brushing.

[0018] Optionally, step 2 further comprises:

[0019] Step 2.1, dissolving polybenzimidazole in a polar aprotic solvent to obtain a polybenzimidazole solution;

[0020] Step 2.2, the binder is dissolved in water, a polar aprotic solvent and a fluorinated surfactant to obtain a binder solution;

[0021] Step 2.3, dissolving the catalyst in a polar aprotic solvent to obtain a catalyst solution;

[0022] Step 2.4, mixing the polybenzimidazole solution, the binder solution and the catalyst solution;

[0023] The polar aprotic solvent is any one of dimethyl sulfoxide, acetonitrile and dimethylformamide; the fluorine surfactant is any one of FC-4430 and FC-003.

[0024] The present invention also provides a catalyst layer of a high-temperature proton exchange membrane fuel cell obtained by the above-mentioned preparation method.

[0025] Compared with the prior art, the technical solution of the present invention has at least the following beneficial effects:

[0026] The quaternized polybenzimidazole (QAPBI) obtained by the quaternization reaction of polybenzimidazole (OPBI) and glycidyl trimethylammonium chloride (GTMAC) is introduced into the catalyst layer. Since the intermolecular force between the quaternary ammonium group in QAPBI and phosphoric acid (634.7 kJ / mol) is much larger than the hydrogen bond force between water molecules and phosphoric acid (52.7 kJ / mol), the phosphoric acid can be effectively fixed in the proton exchange membrane against the hydrogen bond, making it difficult for phosphoric acid to enter the catalyst layer with water molecules. The distribution of phosphoric acid in the catalyst layer is effectively regulated, the coverage of phosphoric acid on the active sites of the catalyst is reduced, and the migration and loss of phosphoric acid from the proton exchange membrane is reduced, thereby ensuring the proton transfer efficiency of the proton exchange membrane, thereby improving the performance of the high-temperature proton exchange membrane fuel cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The polarization characteristic curves of the membrane electrodes prepared in Examples 1-3 of the present invention and Comparative Example 1 are shown.

[0028] Figure 2 Impedance spectra of membrane electrodes prepared in Examples 1-3 of the present invention and Comparative Example 1.

[0029] Figure 3 The relaxation time distribution diagram of the electrochemical impedance spectroscopy of the membrane electrodes prepared in Examples 1-3 of the present invention and Comparative Example 1 is shown.

[0030] Figure 4 Cyclic voltammetry curves of membrane electrodes prepared in Examples 1-3 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0031] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] In the description of the present invention, it should be noted that the terms "upper", "lower", "left", "right", "vertical", "horizontal", "inner", "outer", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", and "third" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance.

[0033] As described in the background technology, phosphoric acid will enter the catalytic layer, contact the catalyst and form a liquid film on its surface, covering the active sites of the catalyst and reducing its reaction activity; in addition, the uneven distribution of phosphoric acid in the catalytic layer will increase the material transfer resistance in the catalytic layer; and due to the hydrogen bonding between water molecules and phosphoric acid, phosphoric acid is easily lost from the proton exchange membrane along with the water molecules, thereby reducing the proton transfer efficiency of the proton exchange membrane and the performance of HT-PEMFC.

[0034] In order to improve the performance of HT-PEMFC, the present invention introduces quaternized polybenzimidazole (QAPBI) obtained by quaternization reaction of polybenzimidazole (OPBI) and glycidyl trimethylammonium chloride (GTMAC) into the catalyst layer. Since the intermolecular force between the quaternary ammonium group in QAPBI and phosphoric acid is much greater than the hydrogen bond force between water molecules and phosphoric acid, it can effectively resist the hydrogen bond effect to fix phosphoric acid in the proton exchange membrane, making it difficult for phosphoric acid to enter the catalyst layer with water molecules, effectively adjusting the distribution of phosphoric acid in the catalyst layer, reducing the coverage of phosphoric acid on the active sites of the catalyst, and reducing the migration and loss of phosphoric acid from the proton exchange membrane, thereby ensuring the conduction of the proton exchange membrane. Specifically, the present invention provides a method for preparing a catalyst layer of a high-temperature proton exchange membrane fuel cell, the method comprising:

[0035] Step 1: using glycidyl trimethyl ammonium chloride and polybenzimidazole as reactants to undergo a quaternization reaction to obtain quaternized polybenzimidazole.

[0036] A certain mass of polybenzimidazole (OPBI) is dissolved in a polar aprotic solvent to obtain a polybenzimidazole solution, the dissolution temperature is 60°C-70°C, and the dissolution time is 6h-8h. Then a certain mass of glycidyl trimethyl ammonium chloride (GTMAC) is added to the polybenzimidazole solution to undergo a quaternization reaction to obtain a quaternized polybenzimidazole solution, the reaction temperature is 90°C-100°C, and the time is 12h-14h. By adjusting the mass ratio of glycidyl trimethyl ammonium chloride (GTMAC) and polybenzimidazole (OPBI), quaternized polybenzimidazole (QAPBI) with different grafting degrees can be obtained. In some embodiments, the mass ratio of glycidyl trimethyl ammonium chloride to polybenzimidazole is (1-2): (98-99). Since the intermolecular force between the quaternary ammonium group and phosphoric acid in QAPBI is much greater than the hydrogen bond force between water molecules and phosphoric acid, the phosphoric acid can be fixed in the proton exchange membrane, making it difficult for phosphoric acid to enter the catalytic layer with water molecules, reducing the coverage of phosphoric acid on the active sites of the catalyst, and at the same time reducing the migration and loss of phosphoric acid from the proton exchange membrane, thereby ensuring the proton transfer efficiency of the proton exchange membrane.

[0037] Step 2: mixing the quaternized polybenzimidazole, the binder and the catalyst to obtain a uniform catalyst slurry.

[0038] A certain amount of binder is dissolved in water, polar aprotic solvent and fluorinated surfactant to obtain a binder solution, and a certain amount of catalyst is dissolved in a polar aprotic solvent to obtain a catalyst solution. The excellent hydrophobicity of the binder improves the gas transmission of the catalyst layer, but its solubility in water and polar aprotic solvents is low. Adding fluorinated surfactant helps to enhance the hydrophilicity of the binder surface and improve the uniformity of the binder solution.

[0039] In some embodiments, the polar aprotic solvent is any one of dimethyl sulfoxide, acetonitrile, and dimethylformamide; and the fluorinated surfactant is any one of FC-4430 and FC-003.

[0040] In some embodiments, the binder includes at least one of polytetrafluoroethylene, perfluorosulfonic acid resin, and vinylidene fluoride-hexafluoropropylene copolymer, and the catalyst includes at least one of a platinum-based catalyst and a platinum alloy catalyst.

[0041] In some embodiments, the mass ratio of quaternized polybenzimidazole to binder is 1:(1-5).

[0042] After the quaternized polybenzimidazole solution, the binder solution and the catalyst solution are mixed, the catalyst slurry is obtained by cyclic stirring and ultrasonication. The purpose of cyclic stirring and ultrasonication is to improve the uniformity of the catalyst slurry. The single stirring time is 10min-20min, and the single ultrasonication time is 15min-60min. In some embodiments, the mass fraction of the total mass of the quaternized polybenzimidazole and the binder in the uniform catalyst slurry is 20%-30%.

[0043] Step 3: coating the uniform catalyst slurry onto carbon paper to obtain a catalyst layer.

[0044] In some embodiments, the coating method is any one of spraying, dipping, and brushing. Spraying is to use a pneumatic spraying device to evenly spray the catalyst slurry on the surface of the carbon paper, dipping is to immerse the carbon paper in the catalyst slurry, and brushing is to evenly coat the catalyst slurry on the surface of the carbon paper with a brush. After the coating is completed by the above method, the carbon paper is dried to obtain the catalyst layer.

[0045] Example 1

[0046] Preparation of quaternized polybenzimidazole solution: first dissolve a certain mass of polybenzimidazole in dimethyl sulfoxide to obtain a polybenzimidazole solution, the dissolution temperature is 60°C, and the dissolution time is 6 hours. Then, add 1g of glycidyl trimethylammonium chloride to 99g of the polybenzimidazole solution to undergo a quaternization reaction to obtain a quaternized polybenzimidazole solution. The reaction temperature is 90°C and the time is 12 hours.

[0047] Preparation of catalytic layer: a certain mass of polytetrafluoroethylene is dissolved in water, FC-4430 and dimethyl sulfoxide to obtain a polytetrafluoroethylene solution, and a certain mass of catalyst is dissolved in dimethyl sulfoxide to obtain a catalyst solution, and then 20g of polytetrafluoroethylene solution and quaternized polybenzimidazole solution (the mass ratio of polytetrafluoroethylene to quaternized polybenzimidazole is 3:1) are added to 80g of the catalyst solution, and stirring and ultrasonication are circulated, stirring for 10 minutes, ultrasonication for 40 minutes, and the cycle is repeated 3 times to obtain a uniform catalyst slurry, and finally the catalyst slurry is evenly sprayed onto the surface of carbon paper using a pneumatic spraying device, and the catalytic layer is obtained after the carbon paper is dried.

[0048] Example 2

[0049] The preparation method of the quaternized polybenzimidazole solution and the catalyst layer is the same as that of Example 1, except that the mass ratio of polytetrafluoroethylene to quaternized polybenzimidazole is replaced with 1:1.

[0050] Example 3

[0051] The preparation method of the quaternized polybenzimidazole solution and the catalyst layer is the same as that of Example 1, except that the mass ratio of polytetrafluoroethylene to quaternized polybenzimidazole is replaced with 1:3.

[0052] Comparative Example 1

[0053] Preparation of catalytic layer: a certain mass of polytetrafluoroethylene is dissolved in water, FC-4430 and dimethyl sulfoxide to obtain a polytetrafluoroethylene solution, and a certain mass of catalyst is dissolved in dimethyl sulfoxide to obtain a catalyst solution, and then 20g of polytetrafluoroethylene solution is added to 80g of catalyst solution, and cyclic stirring and ultrasonication are performed, stirring for 10 minutes, ultrasonication for 40 minutes, and the cycle is repeated 3 times to obtain a uniform catalyst slurry, and finally the catalyst slurry is evenly sprayed onto the surface of carbon paper using pneumatic spraying equipment, and the catalytic layer is obtained after the carbon paper is dried.

[0054] The catalyst layers in Examples 1-3 and Comparative Example 1 were prepared into membrane electrodes and subjected to the following off-line and on-line tests:

[0055] With reference to GB / T 20042.5-2009, polarization curve test of membrane electrode was carried out, and the specific operating conditions were as follows: operating temperature was 160°C, pure hydrogen was fed to the anode, oxygen was fed to the cathode at normal pressure, and the cathode / anode feed ratio was 1:1.

[0056] Referring to GB / T 20042.5-2009, the membrane electrode was subjected to cyclic voltammetry test. The specific operating conditions were as follows: the operating temperature was 160°C, the anode was fed with pure hydrogen, the cathode was fed with nitrogen at normal pressure, and the cathode / anode feed ratio was 1:1.

[0057] The impedance test of the membrane electrode was carried out according to GB / T 20042.5-2009. The specific operating conditions were as follows: the operating temperature was 160°C, the anode was fed with pure hydrogen, the cathode was fed with atmospheric pressure oxygen, the cathode / anode feed ratio was 1:1, and the discharge current density was 0.5A cm -2 .

[0058] like Figure 1 As shown, at low current density, the membrane electrode polarization loss of Examples 1-3 is equivalent to that of Comparative Example 1. At high current density, the membrane electrode polarization loss of Example 1 is smaller than that of Comparative Example 1, and the membrane electrode polarization loss of Examples 2-3 is slightly larger than that of Comparative Example 1, indicating that when the proportion of QAPBI is smaller, the power density of the fuel cell is higher and the performance is better.

[0059] like Figure 2As shown, as the proportion of QAPBI gradually increases, the impedance gradually decreases. This is because the increased QAPBI effectively regulates the distribution of phosphoric acid and improves the proton transfer efficiency; but since QAPBI itself has a dense structure and a strong adsorption effect on phosphoric acid, the increase in QAPBI will also cover the catalyst and increase the cathode polarization. Compared with the membrane electrode of Comparative Example 1, the membrane electrode of Examples 1-3 has a reduced impedance and improved proton transfer efficiency. When the proportion of QAPBI is small, the cathode polarization can be reduced.

[0060] like Figure 3 As shown in the figure, as the proportion of QAPBI gradually increases, the integral impedance of proton transfer gradually decreases, and the integral impedance of oxygen reduction reaction (ORR) gradually increases. Compared with the membrane electrode of comparative example 1, the membrane electrode of example 1 has less effect on oxygen reduction reaction (ORR) and improves the ability of proton transfer. Although the membrane electrodes of examples 2-3 enhance proton transfer, they have a greater effect on oxygen reduction reaction, indicating that when the proportion of QAPBI is small, proton transfer is enhanced without affecting its oxygen reduction reaction.

[0061] like Figure 4 As shown, the electrochemical active area of ​​the membrane electrode can be calculated according to the cyclic voltammetry curve. The electrochemical active areas of the membrane electrodes of Example 1, Example 2, Example 3 and Comparative Example 1 are calculated to be 73.9 m 2 / g, 52.2m 2 / g, 40.1m 2 / g, 65.8m 2 / g, indicating that the membrane electrode of Example 1 can regulate the distribution of phosphoric acid in the catalyst layer and reduce the coverage of phosphoric acid on the active sites of the catalyst, while the membrane electrodes of Examples 2-3 have no obvious effect on regulating the distribution of phosphoric acid in the catalyst layer.

[0062] The above results show that adding a small amount of QAPBI (i.e., a small proportion of QAPBI) to the catalytic layer can reduce membrane electrode polarization losses, improve proton transfer efficiency, and effectively regulate the distribution of phosphoric acid in the catalytic layer, reducing the coverage of phosphoric acid on the active sites of the catalyst.

[0063] In summary, the present invention introduces quaternized polybenzimidazole (QAPBI) into the catalyst layer. Since the intermolecular force between the quaternary ammonium group in QAPBI and phosphoric acid is much greater than the hydrogen bond force between water molecules and phosphoric acid, the phosphoric acid can be fixed in the proton exchange membrane, making it difficult for the phosphoric acid to enter the catalyst layer with the water molecules, effectively adjusting the distribution of phosphoric acid in the catalyst layer, reducing the coverage of phosphoric acid on the active sites of the catalyst, and reducing the migration and loss of phosphoric acid from the proton exchange membrane, ensuring the proton transfer efficiency of the proton exchange membrane, thereby improving the performance and stability of the high-temperature proton exchange membrane fuel cell.

[0064] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.

Claims

1. A method for preparing a catalyst layer of a high-temperature proton exchange membrane fuel cell, characterized in that: The method includes: Step 1, using glycidyl trimethyl ammonium chloride and polybenzimidazole as reactants to undergo a quaternization reaction to obtain a quaternized polybenzimidazole; Step 2, mixing the quaternized polybenzimidazole, the binder and the catalyst to obtain a uniform catalyst slurry; Step 3: coating the uniform catalyst slurry onto carbon paper to obtain a catalyst layer.

2. The method for preparing a catalyst layer of a high temperature proton exchange membrane fuel cell according to claim 1, characterized in that: In the step 1, the temperature of the quaternization reaction is 90° C.-100° C., and the time is 12 h-14 h.

3. The method for preparing a catalyst layer of a high temperature proton exchange membrane fuel cell according to claim 1, characterized in that: In the step 1, the mass ratio of glycidyl trimethyl ammonium chloride to polybenzimidazole is (1-2): (98-99).

4. The method for preparing a catalyst layer of a high temperature proton exchange membrane fuel cell according to claim 1, characterized in that: In the step 2, the binder comprises at least one of polytetrafluoroethylene, perfluorosulfonic acid resin, and vinylidene fluoride-hexafluoropropylene copolymer, and the catalyst comprises at least one of a platinum-based catalyst and a platinum-based alloy catalyst.

5. The method for preparing a catalyst layer of a high temperature proton exchange membrane fuel cell according to claim 1, characterized in that: In the step 2, the mass ratio of the quaternized polybenzimidazole to the binder is 1: (1-5)。 6. The method for preparing a catalyst layer of a high temperature proton exchange membrane fuel cell according to claim 1, characterized in that: In the step 2, the mass fraction of the total mass of the quaternized polybenzimidazole and the binder in the uniform catalyst slurry is 20%-30%.

7. The method for preparing a catalyst layer of a high temperature proton exchange membrane fuel cell according to claim 1, characterized in that: In step 2, the mixing includes stirring and ultrasonic cycles, the single stirring time is 10 min-20 min, and the single ultrasonic time is 15 min-60 min.

8. The method for preparing a catalyst layer of a high temperature proton exchange membrane fuel cell according to claim 1, characterized in that: In step 3, the coating method is any one of spraying, dipping and brushing.

9. The method for preparing a catalyst layer of a high temperature proton exchange membrane fuel cell according to claim 1, characterized in that: The step 2 also includes: Step 2.1, dissolving quaternized polybenzimidazole in a polar aprotic solvent to obtain a polybenzimidazole solution; Step 2.2, the binder is dissolved in water, a polar aprotic solvent and a fluorinated surfactant to obtain a binder solution; Step 2.3, dissolving the catalyst in a polar aprotic solvent to obtain a catalyst solution; Step 2.4, mixing the quaternized polybenzimidazole solution, the binder solution and the catalyst solution; The polar aprotic solvent is any one of dimethyl sulfoxide, acetonitrile and dimethylformamide; The fluorine surfactant is any one of FC-4430 and FC-003.

10. A catalyst layer of a high-temperature proton exchange membrane fuel cell obtained according to the preparation method of claims 1-9.

Citation Information

Patent Citations

  • Ordered membrane electrode and preparation and application thereof

    CN106887598A

  • Method for preparing bipolar membrane based on electrostatic spinning and ultrasonic spraying

    CN114188584A

  • Fuel cell gas diffusion layer and preparation method and application thereof

    CN114628690A

  • Preparation method and application of membrane electrode

    CN114628694A

  • Fluorine-containing polybenzimidazole ionomer, preparation method thereof and membrane electrode

    CN118085284A

Cited By

  • Membrane electrode, preparation method thereof and fuel cell

    CN120955176A